Assessment of wind and wave power characteristic and potential for hybrid exploration in Australia. (October 2022) - Gao, Qiang; Khan, Salman Saeed; Sergiienko, Nataliia; Ertugrul, Nesimi; Hemer, Mark; Negnevitsky, Michael; Ding, Boyin
Abstract: Offshore wind and wave power are abundant energy sources and could provide long term contributions to our future energy supply. The combined exploration of wind and wave power has been proposed as an effective way to mitigate the non-negligible power intermittency and variability of offshore renewables. However, the assessments of wind and wave resources have been developed separately in Australia, and the potential of diversified wind and wave power has not been studied systematically. This study investigates offshore wind and wave energy sources in multiple locations around the Australian coastline and their potentials for integration in terms of energy availability, power variability, coherence and correlation, and annual and seasonal variability over the last seven years. In addition, wind and wave mixed energy farms are studied using commercial wind turbine models and various wave energy converter prototype models. The energy availability, power smoothing effect, capacity factor and downtime of these mixed energy farms are also discussed. Moreover, this paper proposes an effective matrix for assessing the potential of hybrid energy farms in multiple sites in terms of power availability, power variability and combination performance and the sensitivity of selecting various wave energy converter (WEC) models is also investigated to provide a general guideline for future work. The regional comparative results indicate that the swell wave dominated sites in Western and Southern Australia present merits for combining wind and wave power, while wind–wave dominated regions, such as Eastern Australia, are not preferable for this diversified system. It can be found that power variability and downtime can be significantly reduced for the specific wind–wave capacity mix if a lower correlation or longer lag time exists between the two renewables. The results also illustrate that the combinations with different WEC systems present varying benefits in the different locations in Australia. Highlights: Wind and wave energy resources are assessed in Australian region. A wave identification system is designed for hybrid exploration. A matrix to assess the potential of combined energy farm is proposed. Sensitivity of WEC selection to the combined energy farm is investigated.